Sleep Pattern Factors on Premature Skin Aging in YARSI University Medical Students, Force of 2021 - Aprilia, Dhea; Harliansyah; Lilis, Nenden (GoAcademica Research & Publishing, 2024)
Skin aging does not only occur in older people, but skin aging can appear when entering early adulthood or is called premature skin aging. Skin problems such as the appearance of wrinkles and fine lines on the face, apart from that hyperpigmentation can also occur and large pores, are signs of premature skin aging. Lifestyle factors greatly influence the occurrence of premature skin aging, one of which is poor sleep patterns with poor sleep quality. This study aims to test and show the relationship between sleep patterns and premature skin. Quantitative research methods were applied in this research. The research population was students from the Faculty of Medicine, YARSI University Class of 2021, aged 20-25 years. Data collection methods used questionnaires and Janus skin analyzer examination. This research analysis uses cross sectional observational analytics. Statistical analysis revealed a significant relationship between sleep patterns and premature skin aging with the Asymp value. Sig. (2-tailed) < 0.001. Signs of premature skin aging such as fine wrinkles, large pores, hyperpigmentation begin to appear at the age of 20 years. It can be concluded that insufficient sleep time and quality sleep are factors that influence the occurrence of premature skin aging.